(untitled) (Fiep Bulletin - online, 2014)
The current research had as goal to analyze critically the Pedagogical Project of Undergraduate Course in Physical Education from the Federal University from Amapá-UNIFAP, through the predominant concept of vocational training; the record organization; the multidisciplinary characters and; the leading principles and the goals of the course. The obtained results from the document analysis point out to a series of limitations as: man’s dual conception; excessive worry with technical knowledge about body health; a great number of subjects coming from biological/health science and without connotation to the originating knowledge of the human/social science field, earth, philosophy and art and; the body culture is not comprised as an important part of historical heritage and as study object of vocational training in Physical Education directed to several fields of professional performance.